Ответы и объяснения

2013-01-02T16:39:18+00:00

1) решим систему:

a+b=4\1

ab=-6\1

 

a+b=4

ab=-6

 

a=4-b

(4-b)*b=-6

 

a=4-b

4b-b^2=-6

 

a=4-b

b^2-4b-6=0\\b_1=2-\sqrt{10}\\b_2=2+\sqrt{10}

 

a_1=4-(2-\sqrt{10})=2+\sqrt{10}\\a_2=4-(2+\sqrt{10})=2-\sqrt{10}

 

Подставим полученные пары корней в данное выражение:8a-2b(3a-4b):

Ответ:

1)8(2+\sqrt{10})-2(2-\sqrt{10})(3(2+\sqrt{10})-4(2-\sqrt{10}))=164-24\sqrt{10}

 

2)8(2-\sqrt{10})-2(2+\sqrt{10})(3(2-\sqrt{10})-4(2+\sqrt{10}))=164+24\sqrt{10}

 

вроде все) ; ну и задачка(